Future New York Energy Challenges Eye Current Gas Moratorium. Issue 10 (26th April 2019) - Daly, Matthew; Simovic, Uros
Abstract : When New York State launched Reforming the Energy Vision (REV) and its broad regulatory reforms in April 2014, Richard Kauffman (then chairman of energy and finance for New York) stated, "New York is moving to a more market‐based, decentralized approach with how it shapes energy policy. This new approach will help protect the environment, lower energy costs and create opportunities for economic growth … changing the energy industry into a clean, cost‐effective and dynamic system that is more resilient to the impacts of climate change." In the five years since REV, New York has made significant progress on many of its ambitious and laudable goals, such as increasing solar capacity in the state nearly 800 percent from 2012 to 2016, and approving the first offshore wind farm in New York.